The tadpole of Aplastodiscus cavicola (Cruz & Peixoto, 1985) (Amphibia, Anura, Hylidae) - Pezzuti, Tiago Leite; Leite, Felipe Sá Fortes; Pires, Maria Rita Silvério; Garcia, Paulo Christiano De Anchietta (Zootaxa, 2010)
The genus Aplastodiscus Lutz occurs from central and southeastern Brazil to adjacent Argentina and currently comprises 15 species. Faivovich et al. (2005) defined three species groups within the genus: A. albofrenatus, A. albosignatus and A. perviridis. The A. albosignatus group includes A. albosignatus (Lutz & Lutz 1938) A. callipygius (Cruz & Peixoto 1985), A. cavicola (Cruz & Peixoto 1985), A. flumineus (Cruz & Peixoto 1985), A. ibirapitanga (Cruz, Pimenta & Silvano 2003), A. leucopygius (Cruz & Peixoto 1985), and A. sibilatus (Cruz, Pimenta & Silvano 2003). Within this group only A. albosignatus and A. leucopygius have their larval forms described (Peixoto & Cruz 1983; Gomes & Peixoto 2002, respectively).